Optimization and Decision Support Systems for Supply Chains - Póvoa, Ana Paula Barbosa; Corominas, Albert; de Miranda, João Luís (Lecture Notes in Logistics, 2017)
This contributed volume presents a collection of materials on supply chain management including industry-based case studies addressing petrochemical, pharmaceutical, manufacturing and reverse logistics topics. Moreover, the book covers sustainability issues, as well as optimization approaches. The target audience comprises academics, industry managers, and practitioners in the field of supply chain management, being the book also beneficial for graduate students.